The Potential of China's Lacustrine Shale Gas Resources. Issue 2 (March 2013) - Lin, Lamei; Zhang, Jinchuan; Li, Yuxi; Jiang, Shu; Tang, Xuan; Jiang, Shengling; Jiang, Wenli
China is rapidly advancing both theoretical research and practical exploration of her shale gas deposits. Shale gas deposits in China span the gamut of the basic geological features e.g .: marine facies, marine-continental transitional facies, continental facies, and many strata covering the Palaeozoic, Mesozoic, and Cenozoic. Lacustrine shale contained abundant organic matter is mainly developed in the Mesozoic-Cenozoic and is distributed across the North of China, with local occurrences in southern regions. The deposits are characterised by thin monolayer thickness, many inter-beds, large total thickness, rapid lateral variation, varied organic matter types, and a low degree of thermal evolution. The favourable conditions for forming the shale gas enrichment of China's lacustrine organic rich shale mainly include: abundant reservoir porosity, varied organic matter types, large total thickness, good preservation conditions, resource abundance, and favourable surface conditions; the unfavourable conditions mainly include: poor areal continuity, sudden changes in cross-section, and relatively low maturity. At present, continental shale gas exploration of Triassic deposits in the Ordos basin and Jurassic deposits in the Sichuan basin have made significant breakthroughs. Based on the present state of China's shale gas exploration and development, combined with investigation and evaluation, the work demands favourable zone optimisation for China's shale gas resource potential to be best exploited. Shale gas enrichment is considered, not only through determination of the resource's physical boundary with many types and complex geological conditions pertaining to shale gas in China, but in combination with the paucity of shale gas exploration-related geological data and paucity of geological knowledge: the relevant computation parameters are difficult to ascertain accurately, thus the probability volume method is used to evaluate potential continental shale gas strata, including Triassic, Jurassic, Cretaceous and Palaeogene deposits in northern, and north-eastern China, Triassic, Jurassic, Cretaceous, and Palaeogene deposits in northwest regions, some Permian deposits, Jurassic deposits from the upper Yangtze and Dian Qian-Gui(Yunnan-Guizhou-Guangxi) regions, and Jurassic and Palaeogene deposits from the middle-lower Yangtze and southeast region. Estimated continental shale gas resources recoverable in China are 7.92×10 12 m 3, which accounts for 31.59% of her total shale gas recoverable resources. Among them, continental exploitable resource potential is greatest in northern, and northeast regions of China ( c . 3×10 12 m 3, some 37.75% of the total shale gas resource recoverable), followed by the northwest region, the upper Yangtze and Dian-Qian-Gui regions, the middle-lower Yangtze, and the southeast region. Geological resources, and recoverable resources, of Jurassic continental shale gas are the largest ( c . 3.77×10 12 m 3, some 47.6% of the total continental shale gas resource recoverable), followed by Cretaceous, Palaeogene, Triassic, and Permian deposits.